A Welcome to Canadian Association for Work and Labour Studies (CAWLS) Members = Bienvenue aux membres de l’Association canadienne d’études du travail et du syndicalisme (Acets) - Kealey, Gregory S.; Cadigan, Sean (Labour / Le Travail, 2015)
Announces that the journal is now a joint partnership of the Canadian Committee on Labour History with Athabaska University Press, in affiliation with the Canadian Association of Labour Studies.
Issue 76, Fall 2015